Pengaruh Profitabilitas terhadap Harga Saham Perusahaan Keuangan di Bursa Efek Indonesia - I Made Pranata Artha Mulya; Anak Agung Gede Suarjaya (Universitas Veteran Bangun Nusantara, 2024)
Share prices reflect company performance, investors need to pay attention to elements that can influence share prices, one of which is profitability. Profitability is an important indicator for companies, especially in the capital market. Profitability is proxied by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). This research aims to analyze the influence of profitability on the share prices of financial companies on the Indonesian Stock Exchange. The population of financial companies is 53 consisting of the Main Board and Development Board respectively 37 and 16 companies. The sample was selected using the Proportionate Stratified Random Sampling method, the results were 47 companies, consisting of the Main Board and Development Board respectively 33 and 14 companies. Data was collected from company annual financial reports and stock prices from 2020-2022. Data analysis was carried out using the Multiple Linear Regression Analysis technique. The research results show that Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) have a positive and significant effect on the share prices of financial companies on the Indonesian Stock Exchange. The implication of this research is to provide additional information about the ability of the variables Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) to share prices and considerations for investors and related parties who will make decisions.